2021
DOI: 10.3390/pr9040699
|View full text |Cite
|
Sign up to set email alerts
|

The Reversion of DNA Methylation at Coronary Heart Disease Risk Loci in Response to Prevention Therapy

Abstract: Coronary heart disease (CHD) is preventable, but the methods for assessing risk and monitoring response rely on imprecise lipid-based assessments. Recently, we have shown that an integrated genetic–epigenetic test that includes three methylation-sensitive digital PCR assays predicts 3-year risk for incident CHD better than lipid-based methods. However, whether methylation sites change in response to therapies that alter CHD risk is not known. Therefore, we assessed methylation at these three incident CHD-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Previously, we have shown that one of the three MSdPCR measures contained in an integrated genetic–epigenetic test for assessing the 3-year risk for CHD significantly changed as a function of treatment for smoking [ 10 ]. Since smoking is a key driver of CHD [ 11 , 12 ] and smoking cessation therapy can markedly improve survival in smokers with CHD, this suggests that methylation at one of more of the six loci assessed in the PrecisionCHD test may also respond to smoking therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that one of the three MSdPCR measures contained in an integrated genetic–epigenetic test for assessing the 3-year risk for CHD significantly changed as a function of treatment for smoking [ 10 ]. Since smoking is a key driver of CHD [ 11 , 12 ] and smoking cessation therapy can markedly improve survival in smokers with CHD, this suggests that methylation at one of more of the six loci assessed in the PrecisionCHD test may also respond to smoking therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, there is substantial upfront and operational cost for designing, synthesizing, validating, and using these capture probes. Commercial hybridization capture kits of comparable coverage cost >$200 ( 4 ), setting a minimum cost for performing these assays. Furthermore, once a panel is designed, it is inflexible to be applied to other types of diseases or subtypes that have a different set of differentially methylated regions (DMRs).…”
Section: Introductionmentioning
confidence: 99%